The economics of music - Tschmuck, Peter (Economics of big business., 2021)
The music industry is one of the most dynamic business sectors. It has had to evolve and adapt to continually changing technologies and business models. Its latest challenge has been Covid-19 and the loss of live music at a time when live performance outstrips music sales as the primary source of income for today's artists.The second edition of this much used introduction to the economic workings of the music business explores the impact of the pandemic at every level of the sector and considers how the business model may need to change going forward as different stakeholder positions shift. The new edition also examines new trends in the music industry such as the increasing dominance of tech companies and data, the increasing importance of CMOs as market players, the increased role of artist management, which has impacted on new business contracts, as well as changes to how we use music in our everyday lives and how this impacts on new entrepreneurial behaviours around music.